Celeste Thia Kangangi and Julia Ndia - Karurumo village - Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
Celeste Thia Kangani and Julia Ndia are two Kenyan farmers faced with orphaned grandchildren, decreasing yields and old age. They both describe how the weather has changed and there is less rains, but neither knows why these changes have come about. Before sweet potatoes and cassava were planted and used to give high yields, but know this has changed and Celeste and Julia have to use fertilizers for the first time.